HUBUNGAN ANTARA KECERDASAN EMOSI DAN COPING STRESS TERHADAP PSYCHOLOGICAL WELL-BEING PADA ANAK SULUNG DI KELURAHAN X BOGOR - Setianingrum, Naomi Revadani; Maryatmi, Anastasia Sri (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2020)
Psychological well-being is the condition of an individual who is prosperous and able to achieve optimal psychological potential. Emotional quotient is the ability to control yourself, to withstand frustration and to motivate yourself, and to use your emotions positively in dealing with others. Coping stress is the individual’s ability to deal with and adapt to stressful situations, as well as being able to choose appropriate problem solutions. The purpose of this study was to determine the relationship between emotional quotient and coping stress on psychological well-being in the eldest child in Sub-district X Bogor. The sample in this study were 115 subjects with data collection methods using accidental sampling techniques. The measuring instruments used were psychological well-being scale (27 items, α = 0.886), emotional quotient scale (29 items, α = 0.883) and coping stress scale (29 items, α = 0.930). The results showed that there was a positive relationship between psychological well-being and emotional quotient of 0.293 and there was a positive relationship between psychological well-being and coping stress of 0.608. Furthermore, the results of data analysis with multivariate correlation obtained the correlation coefficient Rx1x2y = 0.627 and p = 0.000 (p <0.05). This states that Ho3 is rejected and Ha3 "There is a relationship between emotional quotient and coping stress on psychological well-being in the eldest child in Sub-district X Bogor" accepted.